A Bunch‐Like Tertiary Amine Grafted Polysulfone Membrane for VRFBs with Simultaneously High Proton Conductivity and Low Vanadium Ion Permeability. Issue 8 (13th February 2017) - Tan, Qinglong; Lu, Shanfu; Si, Jiangju; Wang, Haining; Wu, Chunxiao; Li, Xianfeng; Xiang, Yan
Abstract : Polysulfone membranes grafted with bunch‐like tertiary amine groups are successfully synthesized with very high proton to vanadium ion selectivity for vanadium redox flow batteries (VRFBs). The battery with the as‐synthesized membrane demonstrates an impressive Coulombic efficiency of 98.9%, energy efficiency of 90.9%, and outstanding chemical stability, showing promising potential in the development of highly efficient and low‐cost VRFBs. Abstract : Novel polysulfone membranes with bunch‐like tertiary amine groups are synthesized with high ion selectivity and outstanding chemical stability for vanadium redox flow batteries (VRFBs). The bunch‐like tertiary amine groups simultaneously act as an ionic conductor for proton hopping and vanadium ion transport obstacles. The performance of the membrane is tuned via controlling the grafting degree of the chloromethylated polysulfone. The results show that membranes show increasing proton over vanadium ion ( σ/p ) selectivity with increasing functional tertiary groups. VRFBs assembled with the prepared membranes demonstrate an impressive Coulombic efficiency of 98.9% and energy efficiency of 90.9% at a current density of 50 mA cm −2 . Furthermore, the prepared membrane reported in this work shows excellent stability in 1m VO2 + solution at 35 °C over 240 h. Overall, the synthesized polymers provide a new insight into the design of high‐performance membranes toward VRFB applications.